Optimization of Purslane Plant Using Cooking and Pickling Processes for Reducing Oxalate Conten (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Purslane (Portulaca oleracea) is an edible plant rich in benefcial nutrients. Therefore, this study aimed to determine the chemical composition, minerals, fatty acid analysis, phenolic compounds and radical scavenging activity of purslane plant. In addition, the effect of cooking of purslane at different temperatures (60, 80 and 100 °C), for various durations (5, 10, 15 and 20 minute), and pickling for various durations (3, 6 and 9 days) on oxalate content. Sensory evaluation of quality characteristics and fatty acids analysis of biscuits fortified by purslane powder after reducing oxalate content were carried out. Protein, fat, ash and fiber contents of purslane were 5.64, 5.30, 23.42 and 16.03 %, respectively on dry matter basis. The highest concentration mineral was K (4694.0 mg/100g), while the lowest concentration mineral was Zn (0.93 mg/100g). Total phenolic and radical scavenging activity of purslane were 193.22 mg/100g gallic acid equivalent and 87.29 %, respectively. Purslane contains high percentage of unsaturated fatty acids, especially linolenic acid (40.4 % of total fatty acids). On the other hand, the soluble fraction of total oxalate content of purslane cooked for 20 minutes at 60, 80 and 100 °C were 34.65, 19.84 and 15.84 %, respectively. While, the soluble fraction of total oxalate content of purslane pickled for 0, 3, 6 and 9 days were 47.80, 36.23, 25.60 and 14.39 %, respectively. Fortification of biscuits using purslane powder after treatments led to improvement of the quality characteristics of product. Portulaca oleracea could be used as a good source of minerals, antioxidants and omega-3 especially for functional food and nutraceutical applications.